Silver-modified atraumatic restorative technique approach to dental and craniofacial care in Apert syndrome: a case-based perspective - Khatri, Amit; Tyagi, Rishi; Khandelwal, Deepak; Yangdol, Padma; Misbah, Shaikh; Bisht, Harshita; Kumar, Aman (International Journal of Contemporary Pediatrics, 2025)
Apert syndrome is a rare congenital disorder first noted by Wheaton in 1894 and more precisely described by Eugene Apert in 1906. It is primarily characterized by craniosynostosis, midfacial hypoplasia, and complex syndactyly of the hands and feet, along with various systemic and oral abnormalities. The syndrome is estimated to occur in approximately 1 in 1,60,000 live births and typically follows an autosomal dominant inheritance pattern. Most cases are associated with spontaneous mutations in the fibroblast growth factor receptor 2 (FGFR2) gene, which plays a crucial role in bone development and tissue formation. This case report details the clinical and dental management of a 4-year-old female who was diagnosed with Apert syndrome at birth. The patient presented with hallmark craniofacial features such as a high, prominent forehead, flat midface, syndactyly affecting both hands and feet, and notably delayed developmental milestones. She had a history of undergoing multiple surgical interventions, including cranial vault reconstruction to alleviate intracranial pressure and syndactyly release procedures to improve hand functionality. Intraorally, the patient showed maxillary hypoplasia, a high-arched palate, delayed eruption of primary teeth, dental crowding, and multiple carious lesions. Dental care was tailored to her special healthcare needs, utilizing the silver-modified atraumatic restorative technique (SMART), which involves the use of silver diamine fluoride and glass ionomer cement to arrest caries and restore teeth in a minimally invasive manner. A preventive oral health plan, including dietary counselling, fluoride varnish application, and regularly scheduled recall visits, was instituted to maintain long-term dental and overall well-being.